(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The contemporary hospitality industry is increasingly recognizing the importance of nutritional best practices in enhancing guest satisfaction and promoting health-conscious dining. This study explores the outcomes and implications of a comprehensive training program designed for hotel chefs, focusing on nutritional best practices. The training program aimed to equip chefs with the knowledge and skills necessary to integrate healthy cooking techniques, balanced nutrition, and dietary considerations into their culinary practices. Through a mixed-methods approach, including pre- and post-training assessments, interviews, and guest feedback surveys, the study evaluates the effectiveness of the training in improving culinary practices and menu offerings. Results indicate significant improvements in chefs’ understanding of nutritional principles, the incorporation of healthier ingredients, and the creation of more balanced menus. Furthermore, the study highlights the positive impact on guest satisfaction and the potential long-term benefits for hotel operations. The findings underscore the importance of continuous education for culinary professionals in maintaining high standards of nutritional quality and meeting evolving consumer expectations. This research contributes to the growing body of knowledge on the intersection of nutrition and hospitality and offers practical recommendations for implementing successful training programs in the hotel industry.